2018
DOI: 10.1177/1747954118787065
|View full text |Cite
|
Sign up to set email alerts
|

Coaching efficacy, moral disengagement, and responses to hostile aggression among high school coaches

Abstract: This mixed-methods study examined the association between high school sport coaches’ moral disengagement and their perceived coaching efficacy, and began to explore coaches’ justifications of and consequences for the hostile aggression exhibited by their athletes. High school coaches in the United States ( N = 449) completed online surveys that included the Moral Disengagement in Sport Scale, Coaching Efficacy Scale II-High School Teams, and questions regarding their beliefs about and responses to athlete’s ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…The present results indicate that moral disengagement could predict both reactive and proactive aggression after 6 months. This result is in line with the prior finding that there was a positive relationship between moral disengagement and aggression (including reactive and proactive aggression) (Gini et al, 2015; Johnson et al, 2018; Teng et al, 2019), and extend these previous findings by adding longitudinal evidence. Moral disengagement could drive people to achieve the harmful ideas (Bandura, 1999; Bushman & Anderson, 2001), which are involved in both reactive and proactive aggression (Anderson & Bushman, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present results indicate that moral disengagement could predict both reactive and proactive aggression after 6 months. This result is in line with the prior finding that there was a positive relationship between moral disengagement and aggression (including reactive and proactive aggression) (Gini et al, 2015; Johnson et al, 2018; Teng et al, 2019), and extend these previous findings by adding longitudinal evidence. Moral disengagement could drive people to achieve the harmful ideas (Bandura, 1999; Bushman & Anderson, 2001), which are involved in both reactive and proactive aggression (Anderson & Bushman, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a large body of research has supported the view that moral disengagement positively predicted various kinds of aggression such as physical and relational aggression (Kokkinos et al, 2016;Teng et al, 2019;C. Wang et al, 2017), which are involved in both reactive and proactive aggression (Gini et al, 2014(Gini et al, , 2015Johnson et al, 2018). Thus, it is possible that moral disengagement could motivate both reactive and proactive aggression.…”
Section: Effect Of Moral Disengagement On Both Reactive and Proactive...mentioning
confidence: 99%
See 1 more Smart Citation
“…This significant correlation between coach behavior and moral decision-making levels of athletes has led the researchers to investigate the subject deeply. When the studies in other countries are evaluated, it is seen that the number of studies on this matter has increased (Delrue et al, 2017;Johnson et al, 2018); however, it is also seen that the studies carried out in Turkish culture are still in a limited level (Gürpınar, 2014;Gençer et al, 2019;Gümüş, 2019;Y. Yıldız, K. Yıldız, & Tutucu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen in the study by Garay, Carrasco and Amor (2016) that the relationship between anger, hostility and aggression is mediated by moral disengagement. According to Johnson, Vargas, Watson, Pedersen (2018), most coaches indicated that hostile aggression was never unacceptable or justified, and the most common results of hostile aggression in athletes were detected as reduced playing time and additional physical conditioning. Albouza, d'Arripe-Longueville, Corrion (2017) argued in their study that moral values have relationship to aggression.…”
Section: Introductionmentioning
confidence: 99%